Akumulasi Logam Berat Timbal dan Seng dalam Kiambang dan Azolla Menggunakan Rakit Apung Aquatic Plant Di Sungai Siak Kota Pekanbaru - Sulastri Yenita Putri; Budijono Budijono; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractAquatic plant such as Salvinia molesta and Azolla microphylla are able to absorb heavy metals from aquatic environment. As the Senapelan River, a tributary of the Siak River in Pekanbaru is polluted due to anthropogenic activities, the aquatic plant living in that river may absorb heavy metals originated from the pollutant. To understand thePb and Zn content in S. molesta and A.microphylla planted in floating raft in that river, a study has been conducted on   March-April 2017. There was a wooden raft (2 x 5 m) that was completed with used plastic bottles as buoy. The raft was divided into 10 squares (1 x 1 m).  Five squares were used to plant S. molesta(500 grams/ square) and the others were used to plant A. microphylla (500 grams/ square). The plants were sampled once/ 6 days for a month period.Results shown that the heavy metal content in the water was Pb (0.7255 mg/L) and Zn (0.1779 mg/L).In S. molesta Pb and Zn were 7.5181 mg/kg and 5,5390mg/kg. While the average content of Pb and Zn in A. microphyllawere 10.6171 mg/kg and 10,7928 mg/kg respectively. The Pb and Zncontent in these aquatic plant was relatively high.Keywords: heavy metal, aquatic plant, phytoremediation, river pollution